FAKTOR RISIKO KEJADIAN DISLIPIDEMIA PADA LANSIA (Studi Kasus Kontrol Pada Lansia di Poli Lansia RSUD. Bangkinang Kabupaten Kampar Tahun 2016–2017) - Lestari, Ayuning; Handini, Myrnawati Crie; Sinaga, Taruli Rohana (Jurnal Riset Hesti Medan, 2018)
Based on the data from the Central Bureau of Statistics in 2014, the population of the elderly reached 20.24 million or 8.03% of the whole Indonesian people. The older a person is, the more vulnerable he is to degenerative diseases, and one of them is dyslipidemia. The objective of the research was to find out the risk factor for the incidence of dyslipidemia and to determine the value of Odds Ratio of risk factor for dyslipidemia. The research used case-control study design. The data were gathered from patients’ medical records and from the respondents. The samples were 135 respondents with 45 of them were in case group and 90 of them were in control group. The result of bivariate analysis showed that all independent variables were correlated with the incidence of dyslipidemia (p<0.05). The result of multivariate analysis showed that the variable which had the most dominant correlation  was smoking habit at p-value = 0.000 (p<0.05) and OR-value = 9.929 (85% CI 3.428-28.762) which indicated that smoking habit was the most influential risk factor for the incidence of dyslipidemia in the elderly. Keywords: The Elderly, Dyslipidemia, Gender, Obesity, Diabetes Mellitus, Smoking